Nursing Student Psychological Experience in Working on Thesis - Rahmi Imelisa; Khrisna Wisnusakti (HealthCare Nursing Journal, 2023)
Psychologic respon is how someone respons to stressors. To cope with the stressors, someone will react to achieve a self-equilibrium to survive. One of stressors that a college student faced is to finished their thesis, as their final task. Many psychological responses happened along with the thesis process. This research aimed to explore the psychological experiences of students while working on their thesis. This research was a qualitative method with a phenomenology approach. The researcher conducted a depth-intervieuw to 5 participants, who were a final-year student of Nursing Sciences Study Program in a College at Cimahi City. This research used a Collaizi Method to analyzed data to find the themes. Five themes generated in this research, that is 1) Student’s anxiety while working on the thesis, 2) Impact of the thesis process on student’s physical health, 3) The impact of thesis process on student behavior, 4) Student’s coping mechanisms during the thesis process, and 5) Student expectation regarding the thesis process. It is recommended for students to improve their coping skills while working on their thesis to prevent serious mental health problems and it is expected that thesis supervisors and study program to make an efforts to prevent mental health problems in students whose are completing their thesis.